Evaluation Of The Impact Of The National Health Insurance Program On The Quality Of Primary Services: A Literature Review - Dewi Agustina; Tiur Dini Hariani Simbolon; Meliani Putri Inayah; Sabila Yassarah; Siti Husnah; Ayu Diah Aftri; Aulia Farah Dina; Dita Chania Tri Irsan; Khairuna Pratiwi; Dinda Syahbania; Eni Karlina; Nabilah Risti Ameliya; Nasywa Azzahra Siregar (Universitas Muhammadiyah Palu, 2026)
The National Health Insurance Program (JKN) has improved access to and utilization of primary health care services; however, the quality of care at many primary health care facilities (FKTP) has not always improved, making it necessary to evaluate the impact of JKN on the quality of primary care. This study aims to evaluate the impact of JKN on the quality of primary care through a literature review. The study employs a literature review approach with a critical qualitative-descriptive design, utilizing national and international journals, theses, dissertations, reports, and JKN policy documents accessed via Google Scholar, Garuda, and SINTA, analyzed using content analysis and narrative synthesis techniques. The results indicate that JKN improves access to and utilization of primary care services and encourages the implementation of quality assurance standards and systems in Primary Health Care Facilities (FKTP); however, in some areas, service quality is hindered by delays, long waiting times, and limitations in personnel and facilities, resulting in suboptimal patient experiences and satisfaction. Thus, JKN has the potential to improve the quality of primary care if accompanied by capacity building at primary health care facilities (FKTP), consistent regulations, and resource allocation.